Impact of Oscillating Positive Expiratory Pressure Device Use on Post-Discharge Hospitalizations: A Retrospective Cohort Study Comparing Patients with COPD or Chronic Bronchitis Using the Aerobika® and Acapella® Devices - Tse J (International Journal of COPD, 2020)
Jenny Tse,1 Keiko Wada,1 Yi Wang,1 Dominic Coppolo,2 Vladimir Kushnarev,3 Jason Suggett3 1IQVIA, Medical and Scientific Services, Real World Solutions, Cambridge, MA, USA; 2Monaghan Medical Corporation, Clinical Strategy and Development, Plattsburgh, NY, USA; 3Trudell Medical International, Science and Technology, London, ON, CanadaCorrespondence: Jenny TseIQVIA, 201 Broadway, 5th Fl, Cambridge, MA 02139, USATel +1 617-583-0627Email Jenny.Tse@iqvia.comPurpose: Managing and preventing disease exacerbations are key goals of COPD care. Oscillating positive expiratory pressure (OPEP) devices have been shown to improve clinical outcomes when added to COPD standard of care. This retrospective database study compared real-world resource use and disease exacerbation among patients with COPD or chronic bronchitis prescribed either of two commonly used OPEP devices.Patients and methods: Patients using the Aerobika® (Trudell Medical International, London, ON, Canada) or Acapella® (Smiths Medical, Wampsville, New York, USA) OPEP device for COPD or chronic bronchitis were identified from hospital claims linked to medical and prescription claims between September 2013 and April 2018; the index date was the first hospital visit with an OPEP device. Severe disease exacerbation, defined as an inpatient visit with a COPD or chronic bronchitis diagnosis, and all-cause healthcare resource utilization over 30 days and 12 months post-discharge were compared in propensity score (PS)-matched Aerobika device and Acapella device users.Results: In total, 619 Aerobika device and 1857 Acapella device users remained after PS matching. After discharge from the index visit, Aerobika device users were less likely to have ≥ 1 severe exacerbation within 30 days (12.0% vs 17.4%, p=0.01) and/or 12 months (39.6% vs 45.3%, p=0.01) and had fewer 12-month severe exacerbations (mean, 0.7 vs 0.9 per patient per year, p=0.01), with significantly longer time to first severe exacerbation than Acapella users (log-rank p=0.01). Aerobika device users were also less likely to have ≥ 1 all-cause inpatient visit within 30 days (13.9% vs 20.3%, p< 0.001) and 12 months (44.9% vs 51.8%, p=0.003) than Acapella users.Conclusion: Patients receiving the Aerobika OPEP device, compared to the Acapella device, had lower rates of subsequent severe disease exacerbation and all-cause inpatient admission. This suggests that Aerobika OPEP device may be a beneficial add-on to usual care and that OPEP devices may vary in clinical effectiveness.Keywords: database, exacerbations, re-hospitalization, sputum clearance, OPEP